New orbits for comets C/1843 J1 (Mauvais) and C/1853 W1 (van Arsdale) - Branham, Richard Lacy (2015)
New orbits for comet C/1843 J1 (Mauvais) and comet C/1853 W1 (van Arsdale) are calculated. Both orbits are hyperbolic, with e = 1.001145 and semi-major axis a = -1412.18 AU for Mauvais and e = 1.000700 and a = -2919.24 AU for van Arsdale. Integrating the orbits backwards indicate that both comets were born in the far Oort cloud.